PENGARUH PENDEKATAN PROJECT BASED LEARNING TERHADAP KEMAMPUAN KOMUNIKASI MATEMATIS DAN DISPOSISI MATEMATIS SISWA SMA NEGERI 1 NGABANG - Ritawati, Bernadeta (Ed-Humanistics : Jurnal Ilmu Pendidikan, 2019)
AbstractThe purposes of this study are: (1) to assess the of a mathematical disposition in a given threedomensional shapes after learning use of Project Based Learning approach; (2) to assess the ofmathematical communication in a given three domensional shapes after learning use of ProjectBased Learning approach; and (3) know the contribution of Project Based Learning approach tomathematical communication in three domensional shapes. The population of this study is alltwelve grade students of SMA Negeri Kabupaten Landak class XII. The selected samples areclass XII students. The results are: (1) the of mathematical disposition and mathematicalcommunication in three domensional shapes after a given learning use Project Based Learningapproach is relatively high; (2) Project Based Learning approach greatly affect of studentsmathematical communication and disposition of in three domensional shapes.Keywords: Project Based Learning, Mathematics Communication, Mathematics Disposition,Geometry